2023
DOI: 10.3390/cardiogenetics13010003
|View full text |Cite
|
Sign up to set email alerts
|

Lower Circulating Cell-Free Mitochondrial DNA Is Associated with Heart Failure in Type 2 Diabetes Mellitus Patients

Abstract: Cell-free nuclear (cf-nDNA) and mitochondrial (cf-mDNA) DNA are released from damaged cells in type 2 diabetes mellitus (T2DM) patients, contributing to adverse cardiac remodeling, vascular dysfunction, and inflammation. The purpose of this study was to correlate the presence and type of cf-DNAs with HF in T2DM patients. A total of 612 T2DM patients were prescreened by using a local database, and 240 patients (120 non-HF and 120 HF individuals) were ultimately selected. The collection of medical information, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…While numerous studies have tested the associations between CVD and mtDNAcn from whole blood, there is a scarcity of data from human cohorts concerning ccf‐mtDNAcn in CVD. Berezina et al 67 . showed that heart failure patients ( N = 120) have higher ccf‐nDNAcn but lower ccf‐mtDNAcn than controls ( N = 120).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While numerous studies have tested the associations between CVD and mtDNAcn from whole blood, there is a scarcity of data from human cohorts concerning ccf‐mtDNAcn in CVD. Berezina et al 67 . showed that heart failure patients ( N = 120) have higher ccf‐nDNAcn but lower ccf‐mtDNAcn than controls ( N = 120).…”
Section: Discussionmentioning
confidence: 99%
“…While numerous studies have tested the associations between CVD and mtDNAcn from whole blood, there is a scarcity of data from human cohorts concerning ccf-mtDNAcn in CVD. Berezina et al 67 showed that heart failure patients (N = 120) have higher ccf-nDNAcn but lower ccf-mtDNAcn than controls (N = 120). In contrast, Liu et al 24,68 measured an increase in mtDNA in diabetic patients with coronary heart disease (CHD) (N = 50) compared to those without CHD (N = 44).…”
Section: Tcfmentioning
confidence: 99%
“…Rosa et al, found that increased ccf-mtDNA levels in diabetes were correlated with elevated cellular mtDNA levels [23]. Another study suggested that ccf-mtDNA could be evaluated as a biomarker of heart failure in patients with T2D [24]. Given these promising results, ccf-mtDNA could have clinical value in the management of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-free circulating DNA (cfcDNA) circulates in two main pools: circular and singlestranded molecules belonging to mitochondrial-derived and nuclear-derived subpopulations, reflecting patterns of DNA methylation and a variety of neutrophil extracellular traps (NETosis) [196,197]. The cfcDNA are determined in subdetectable concentrations under certain physiological conditions, such as physical exercise, whereas increased circulating levels of these fragments are strongly associated with cardiovascular, autoimmune, rheumatic diseases, infections, and malignancy [198][199][200][201][202]. The main causes of cfcDNA production are mitochondrial dysfunction and inflammation, which are powerful drivers of numerous diseases and conditions, including AF [203].…”
Section: Bone-related Proteinsmentioning
confidence: 99%